2021
DOI: 10.1089/dia.2020.0609
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SARS-CoV-2 Antibodies in Children and Adults with Type 1 Diabetes

Abstract: Objective: As diabetes is a risk factor for severe symptoms, hospitalization, and death with COVID-19 disease, we aimed to assess the prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies in children and adults with and without type 1 diabetes in Colorado during 2020. Research Design and Methods: We developed a highly sensitive and specific test for antibodies against SARS-CoV-2 and measured the antibodies in children and adults with new-onset (n = 129) and established type 1 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
1
16
2
Order By: Relevance
“…This study also showed regional differences in the prevalence of antibodies: it is highest in the Brussels region (24%). As in another study [9], our results in the specific population of children with newly diagnosed type 1 diabetes are quite similar to that of the general population.…”
supporting
confidence: 89%
“…This study also showed regional differences in the prevalence of antibodies: it is highest in the Brussels region (24%). As in another study [9], our results in the specific population of children with newly diagnosed type 1 diabetes are quite similar to that of the general population.…”
supporting
confidence: 89%
“…As reported in the literature, an interaction between COVID-19 and glucose-insulin metabolic disorders is postulated in adults [1,29] and not excluded in pediatrics [30,31]. In particular, the relationship between COVID-19 and type 2 diabetes mellitus (T2DM) has been extensively described in adults [1,2,30] and a relationship between SARS-CoV-2 infection and type 1 diabetes mellitus (T1DM) has also been discussed in children [30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Much attention has been paid to the different comorbidities involving individuals infected by SARS-CoV-2 [ 2 , 3 ]. Diabetes is not associated with a higher risk to contract the infection [ 4 , 5 ], but worsens the prognosis of infected people [ 6 ] leading frequently to hospital admission, acute respiratory syndrome and mortality [ 7 , 8 ]. A recent English whole-population analysis showed that both type 1 and type 2 diabetes were independently associated with a more than two-fold increased risk of in-hospital death with COVID-19 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%